Two new species of the Didymopanax clade of Schefflera (Araliaceae) from the Brazilian Amazon - Fiaschi, Pedro; Plunkett, Gregory M. (Phytotaxa, 2016)
Two new species of the largely Brazilian Didymopanax clade of Schefflera (Araliaceae) are here described, illustrated, and compared to similar taxa. Both are from poorly sampled areas in the Brazilian Amazon Basin. Schefflera prancei is known only from the Serra do Divisor National Park, at the border between Brazil and Peru. It differs from the similar S. confusa by its leaflets with narrowly elliptic to oblanceolate blades, with an acuminate to cuspidate apex, and the light brown to grayish sericeous indument on the abaxial blade surface. The second new species, Schefflera pubicarpa, is found in central Amazonian forests, and differs from similar species of the clade by a combination of characters, including a large-tree habit, leaves with 8 to 10 leaflets, inflorescences with ascending secondary branches and lacking tertiary branches, flowers with trichomes along the styles, and pubescent fruits. While this species appears to have a restricted distribution in Brazil, a westward extension reaching into Peru, Colombia, and Ecuador may be likely as new collections from intermediate areas become available.